TNM atlas: illustrated guide to the TNM/pTNM classification of malignant tumours - Hermanek, Paul; Hutter, R. V. P.; Sobin, L. H.; Wagner, Gustav; Wittekind, Ch. (Springer, 1997)
The present edition of the TNM Atlas takes into consideration all additions and changes made in the fifth edition of the TNM Classification of Malignant Tumours and, therefore, represents the current state of the TNM classification as accepted worldwide by all national committees, including the American Joint Committee of Cancer. Numerous illustrations facilitate the practical application of the TMM system for all doctors working in the field of oncology
Keywords: Atlas; TNM-System